2012
DOI: 10.1371/journal.pone.0034743
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on Energy Intake in Fish: The Link between Diet Composition, Energy Metabolism, and Energy Intake in Rainbow Trout

Abstract: The hypothesis was tested that fish fed to satiation with iso-energetic diets differing in macronutrient composition will have different digestible energy intakes (DEI) but similar total heat production. Four iso-energetic diets (2×2 factorial design) were formulated having a contrast in i) the ratio of protein to energy (P/E): high (HP/E) vs. low (LP/E) and ii) the type of non-protein energy (NPE) source: fat vs. carbohydrate which were iso-energetically exchanged. Triplicate groups (35 fish/tank) of rainbow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
70
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 55 publications
9
70
1
Order By: Relevance
“…Feeding the high-fat diet, however, did not decrease the amount of food intake (either considering the absolute amount per fish day or the relative amount corrected for differences in body weight). Other comparable studies carried out with rainbow trout similarly observed no decreased intake due to the higher dietary lipid content (Geurden et al, 2006;Saravanan et al, 2012;Figueiredo-Silva et al, 2012a,b), whereas trout fed with a fish-oil-enriched diet for 15 weeks displayed a significant decrease in food intake (Gélineau et al, 2001). The different response may relate to the difference in feeding duration (4 weeks in the present study) or to the fatty acid amount and composition of the lipids used for preparing the high-fat diet (a mixture of fish oil and rapeseed oil in this study), which together with the amount of lipids ingested, result in fish fed the high-fat diet having an increased intake of several fatty acids, especially myristeate, palmitate, pamitoleate, oleate, linoleate, α-linolenate, eicosapentanoate and docosahexanoate.…”
Section: Effects On Food Intakementioning
confidence: 87%
“…Feeding the high-fat diet, however, did not decrease the amount of food intake (either considering the absolute amount per fish day or the relative amount corrected for differences in body weight). Other comparable studies carried out with rainbow trout similarly observed no decreased intake due to the higher dietary lipid content (Geurden et al, 2006;Saravanan et al, 2012;Figueiredo-Silva et al, 2012a,b), whereas trout fed with a fish-oil-enriched diet for 15 weeks displayed a significant decrease in food intake (Gélineau et al, 2001). The different response may relate to the difference in feeding duration (4 weeks in the present study) or to the fatty acid amount and composition of the lipids used for preparing the high-fat diet (a mixture of fish oil and rapeseed oil in this study), which together with the amount of lipids ingested, result in fish fed the high-fat diet having an increased intake of several fatty acids, especially myristeate, palmitate, pamitoleate, oleate, linoleate, α-linolenate, eicosapentanoate and docosahexanoate.…”
Section: Effects On Food Intakementioning
confidence: 87%
“…However, several other fish studies did not show an equal protein deposition with satiation feeding (e.g., 7,11). The dietinduced difference in the voluntary intake levels observed in various fish species (7,9,(15)(16)(17) might be related to the type and level of dietary nonprotein digestible energy (NPDE) source (starch vs. fat) as suggested in mammals [for review, see (18). The mechanism by which the NPDE source affects voluntary feed intake in fish has been, so far, little explored.…”
Section: Introductionmentioning
confidence: 96%
“…It has often been suggested that fish, like other animals, adjust their voluntary feed intake according to the digestible energy content of the diet in order to meet a predefined energy requirement (2)(3)(4). However, recent findings in rainbow trout (5)(6)(7)(8)(9)(10) and other teleosts (6,11,12) contradict the notion that feed intake is adjusted to have a constant digestible energy intake (DEI) 6 . Similarly, the demand for a target lean growth or protein deposition rather than for a predefined energy requirement has been proposed to regulate feed intake in fish (8,10,13,14).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations